Improvement of Teacher Innovation through Strengthening Organizational Climate in Indonesia - Lusiana Wulansari; Thamrin Abdullah; Eka Suhardi; Sri Setyaningsih (International Journal of Education, Information Technology, and Others, 2023)
This research aims to determine efforts to enhance teacher innovation by examining organizational climate variables' direct influence. The study employed a survey method with a Structural Equation Modeling (SEM) analysis approach. The research sample consisted of 205 teachers selected using proportional random sampling techniques. The researchers employed the data analysis method of action research, utilizing the SEM-PLS tool with WarpPLS software to analyze the data. The research findings concluded that organizational climate has a significant positive direct influence on innovation with a value of β = 0.250 and a p-value < 0.001. In conclusion, this research indicates that the organizational climate influences teacher innovation.